Corporate Social Responsibility Performance and Ownership Structures adding Value to Indonesia’s Banking Sector - Saarce Elsye Hatane; Jessica Hermawan Telim; Revina Tjanlisan; Graciela Agustin Tandiono; Madeline Tjandra (Indonesian Journal of Sustainability Accounting and Management, 2021)
This research examines the link between corporate social responsibility (CSR) and ownership structure on firm value to encourage sustainability of the banking industry in Indonesia. The study uses the Kinder, Lydenberg, and Domini’s (KLD) assessment to evaluate CSR in the banking sector in Indonesia, and further, it uses economic value added to assess a firm’s value. This research studied 37 banks in Indonesia from 2013 to 2018. The research model employed weighted least square panel tests. Results reveal that the CSR influence is significantly positive for firm value. However, other ownership structures that have a similar effect on firm value are government ownership and foreign institutional ownership. The results further indicate that CSR can be a means of communication and can form a part of a bank’s strategy to enhance value, especially the elements of diversity, environment, and products. Moreover, this research finding provides decision-makers with in-depth knowledge regarding the beneficial effects of ownership structure on company value. The study develops the results from previous studies by discussing each component of CSR performance in the KLD and determines that each component has a varying effect on firm value.